UMP Foundation to aid students in need - Mimi Rabita, Abdul Wahit (2020)
Pekan, 3rd October 2020 – Universiti Malaysia Pahang (UMP) Foundation has taken the initiative to alleviate the burden faced by the students due to the Ministry of Higher Education (MoHE) decision to postpone the physical and face-to-face registration by providing emergency assistance incentive to those affected.